Role of myeloperoxidase in the killing of Naegleria fowleri by lymphokine-altered human neutrophils. - Ferrante, A (1987)
Previously we have shown that human neutrophils treated with conditioned medium from phytohemagglutinin-stimulated mononuclear leukocytes (sCM) in the presence of antisera have amoebicidal properties for Naegleria fowleri, a pathogenic free-living amoeba. The data now presented show that neutrophils which lack myeloperoxidase (MPO) but have a normal oxygen-dependent respiratory burst could not be altered by sCM to express the amoebicidal activity. Catalase inhibited this amoebicidal activity of sCM-treated neutrophils. Various components and products of the neutrophils were examined for effects on naegleriae. A granule extract was found to have no effect at concentrations up to 100-fold that which killed Salmonella minnesota R595. Hydrogen peroxide appeared to have little effect even at 100 microM. However, in the presence of MPO, H2O2 was amoebicidal at 2.5 microM. The generation of amoebicidal activity required the presence of chloride ions. Azide inhibited the effects of the MPO-H2O2-Cl- system. Arginine, a scavenger of hypochlorite, significantly depressed the ability of sCM-treated neutrophils to kill amoebae and also prevented the amoebicidal properties of the MPO-H2O2-halide system. These results suggest that the MPO-H2O2-halide system is important in the killing of naegleriae by sCM-treated neutrophils and that hypochlorite may be the amoebicidal agent.